Working in the health sector: implementation of workplace health promotion - Eliana Castro S; Alba Idály Muñoz S (Universidad de Antioquia, 2011)
Objective: to discuss issues that are relevant to the implementation of workplace health promotion (whp) in organization processes of the health sector as a strategic tool to manage health and safety at the workplace. Methods: after a conceptual review of whp in 2009, a qualitative case study on the development of this strategy in third level hospitals of Bogotá was carried out. This descriptive and cross-sectional study was approved by the Ethics Committee of the Faculty of Nursing at the National University of Colombia. Results: although there are occupational health programs that convey the spirit of whp in their content, its level of development is not consistently linked to it. The following criteria were analyzed: strategy and commitment, human resources and organization, social responsibility, planning, and development and results, all of which were not well valued by workers. Final considerations: the traditional approach to occupational health and the poor integration of the WHP principles into organizational processes are reflected in the actions taken and the expectations regarding the subject. Therefore, actions should be taken in terms of public policies to strengthen the institutional capacity to ensure the feasibility of whp in the health sector.